Gambaran Kelengkapan Pengisian Rekam Medis Elektronik Gigi di RSUP Prof. Dr. R. D. Kandou Manado Tahun 2023-2024 - Veronica, Regina R.; Khoman, Johanna A.; Wahyuni, Rizka (e-GiGi, 2026)
Abstract: Along with technological advances, the Electronic Medical Record (EMR) system has begun to be widely implemented, including in dental services. This system has been proven to improve the efficiency, safety, and quality of health services. However, its implementation still faces various challenges. Incompleteness in filling out the EMR can impact the accuracy of diagnosis, the effectiveness of treatment, as well as the legal and ethical aspects of the profession. In the field of dentistry, completeness of fields such as odontograms, treatment notes, and supporting attachments is crucial to ensure comprehensive and quality services. This study aims to determine the completeness of filling out the electronic dental medical record at Prof. Dr. R. D. Kandou Manado General Hospital in 2023-2024. This type of research is descriptive observational using a simple random sampling method with a population of all patient electronic dental medical record data at Prof. Dr. R. D. Kandou Manado General Hospital in 2023-2024. The results showed that the completeness of the electronic dental medical record section of the patient's identity, odontogram, dental treatment table, supplementary/supporting sheets in 2023-2024 has been completely filled out. In conclusion, the completeness of filling out the electronic dental medical record at Prof. Dr. R. D. Kandou Hospital has been achieved completely. Keywords: completeness; electronic dental medical record; hospital    Abstrak: Seiring kemajuan teknologi, sistem Rekam Medis Elektronik (RME) mulai banyak diterapkan, termasuk pada layanan kedokteran gigi. Sistem ini terbukti meningkatkan efisiensi, keamanan, dan kualitas pelayanan kesehatan. Namun, implementasinya masih menghadapi berbagai tantangan. Ketidaklengkapan dalam pengisian RME dapat berdampak pada akurasi diagnosis, efektivitas perawatan, serta aspek legal dan etis profesi. Di bidang kedokteran gigi, kelengkapan isian seperti odontogram, catatan perawatan, dan lampiran pendukung sangat penting untuk menjamin pelayanan yang menyeluruh dan berkualitas. Penelitian ini bertujuan untuk mengetahui gambaran kelengkapan pengisian rekam medis elektronik gigi di RSUP Prof. Dr. R. D. Kandou Manado tahun 2023-2024. Jenis penelitian ini yaitu deskriptif observasional menggunakan metode simple random sampling dengan populasi seluruh data rekam medis elektronik gigi pasien di RSUP Prof. Dr. R. D. Kandou Manado pada tahun 2023-2024. Hasil penelitian menunjukkan kelengkapan rekam medis elektronik gigi bagian identitas pasien, odontogram, tabel perawatan gigi, lembar pelengkap/penunjang pada tahun 2023-2024 sudah terisi lengkap. Simpulan penelitian ini ialah kelengkapan pengisian rekam medis elektronik gigi di RSUP Prof. Dr. R. D. Kandou Manado sudah terisi lengkap. Kata kunci: kelengkapan; rekam medis gigi elektronik; rumah sakit